The Relationship between Anxiety Level and Cognitive Function of Students Class of 2022 Medical Faculty of Universitas Palangka Raya in Dealing with OSCE - Surbakti, Ranintha; Mutiasari, Dian; Sugiono, Yulinar N; Jelita, Helena; Tindaon, Debora; Kusuma, Wijaya (Universitas Kristen Maranatha, 2024)
Anxiety is a feeling that is often felt in dealing with various life situations that occur to a person. This can also happen to new students taking the Objective Structured Clinical Examination (OSCE). Anxiety that is continuously experienced by students will disrupt their sleep patterns, and lack of sleep results in poor sleep quality which can affect the cognitive and psychomotor aspects of medical students. This study aims to determine the relationship between anxiety levels and students' cognitive function in dealing with OSCE. This research is a cross-sectional study, where the research subjects are students from the class of 2022 who meet the exclusion and inclusion criteria. The research was conducted in June 2023 at the Faculty of Medicine, University of Palangka Raya. This research was conducted on 135 subjects consisting of 41 men and 94 women with an average age of 19(17-21) years. The highest anxiety level before the OSCE exam in the study was a moderate anxiety level of 75.5%. There is no significant relationship between anxiety level (ZSAS score) and cognitive function (Moca-Ina) with p=0.680. In conclusion, there is no relationship between anxiety level and students' cognitive function in dealing with OSCE.